2023
DOI: 10.1111/trf.17396
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease and the need for blood: Barriers to donation for African, Caribbean, and Black young adults in Canada

Jennie Haw,
Jean Walrond,
John Jayachandran
et al.

Abstract: Background: Many blood operators around the world face the challenge of increasing the number of donors of African ancestry to meet the transfusion needs of people living with sickle cell disease. This article reports results of the barriers to blood donation for young adults (aged 19-35) in Canada who identify as African, Caribbean, or Black. Study Design and Methods: A community-based qualitative study was conducted by researchers from community organizations, blood operator, and universities. In-depth focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the study conducted by Chin et al (2018), the most prevalent barrier to blood donation was fear of needle prick, pain, or discomfort (45.3%). People are willing to donate blood within their community when they know there's a need, but the barriers to donation vary by context and population, so it's important to understand these barriers locally for specific groups (Haw et al, 2023). According to Mishra (2016), the same conclusion was reached in other studies in which the majority of respondents feared needles and needle insertion pain.…”
Section: Introductionmentioning
confidence: 76%
“…In the study conducted by Chin et al (2018), the most prevalent barrier to blood donation was fear of needle prick, pain, or discomfort (45.3%). People are willing to donate blood within their community when they know there's a need, but the barriers to donation vary by context and population, so it's important to understand these barriers locally for specific groups (Haw et al, 2023). According to Mishra (2016), the same conclusion was reached in other studies in which the majority of respondents feared needles and needle insertion pain.…”
Section: Introductionmentioning
confidence: 76%
“…Thus, the limited availability of phenotypically matched RBCs from donors of African ancestry is an important alloimmunisation risk factor in SCD patients. To enhance the recruitment of ethnic minorities in Western countries, studies focused on barriers and motivators to blood donation have revealed significant differences between Caucasian-and African-descent respondents and have advocated dedicated campaigns [14,15]. This imbalance between supply and demand is particularly acute for the highly polymorphic RH and Kell blood group systems, for which recipient/donor compatibility is critical in transfusion practices; consequently, most alloantibodies described in SCD patients are directed against the Rh and Kell systems [10,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%